2006
DOI: 10.1099/mic.0.28699-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, phylogeny and evolution of ribulose-1,5-bisphosphate carboxylase/oxygenase genes in obligately chemolithoautotrophic sulfur-oxidizing bacteria of the genera Thiomicrospira and Thioalkalimicrobium

Abstract: The occurrence of the different genes encoding ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO), the key enzyme of the Calvin-Benson-Bassham cycle of autotrophic CO 2 fixation, was investigated in the members of the genus Thiomicrospira and the relative genus Thioalkalimicrobium, all obligately chemolithoautotrophic sulfur-oxidizing Gammaproteobacteria. The cbbL gene encoding the 'green-like' form I RubisCO large subunit was found in all analysed species, while the cbbM gene encoding form II RubisCO w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
1
22
2
1
Order By: Relevance
“…Despite the good results previously obtained with these primers for the haloalkaliphilic SOB (Tourova et al, 2006(Tourova et al, , 2007, they gave positive amplification among the halophilic SOB only for representatives of the genera Halothiobacillus, Thiohalomonas, Thiohalophilus and Thiohalobacter. Of the other primer pairs tested (Table 1), the one specific for the 'green-like' form IA (Alfreider et al, 2003) gave the best results, but the amplified cbbL fragment only had a small overlap with the fragments obtained with the RubIgF/RubIgR primers and with most of the cbbL sequences deposited in GenBank.…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…Despite the good results previously obtained with these primers for the haloalkaliphilic SOB (Tourova et al, 2006(Tourova et al, , 2007, they gave positive amplification among the halophilic SOB only for representatives of the genera Halothiobacillus, Thiohalomonas, Thiohalophilus and Thiohalobacter. Of the other primer pairs tested (Table 1), the one specific for the 'green-like' form IA (Alfreider et al, 2003) gave the best results, but the amplified cbbL fragment only had a small overlap with the fragments obtained with the RubIgF/RubIgR primers and with most of the cbbL sequences deposited in GenBank.…”
Section: Resultscontrasting
confidence: 68%
“…(English et al, 1992), Halothiobacillus neapolitanus (Baker et al, 1998), Thiomonas intermedia (Stoner & Shively, 1993) and Thiomicrospira sp. (Tourova et al, 2006). However, most of the evidence was obtained for a single strain of a single species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…it was shown that strain HL 5 T possessed two different cbbL genes of the 'green-like' form I and a cbbM gene of the form II of this enzyme, similar to the other species in the Thiomicrospira crunogena cluster, such as Hydrogenovibrio marinus (Yoshizawa et al, 2004), Thiomicrospira crunogena and Thiomicrospira kuenenii (Tourova et al, 2006). However, the G+C content in the genome of all three halophilic isolates was 56?1-57?1 mol%, which is 5-15 mol% higher than in the Thiomicrospira crunogena group (39?2-51?7 mol%).…”
mentioning
confidence: 75%
“…The Calvin-BensonBassham cycle is the most common carbon fixation pathway for chemolithoautotrophic microorganisms. As one of the key enzymes for the Calvin cycle, Rubisco was particularly used for studying chemoautotrophic SOB in different habitats (Tourova, 2006;Tourova et al, 2010). The increased abundance of carbon fixation genes may be due to the thriving of chemoautotrophic SOB, although further phylogenetic studies are needed to support the hypothesis.…”
Section: Discussionmentioning
confidence: 99%